ALLEVIATION OF CISPLATIN INDUCED NEPHROTOXICITY IN ALBINO RATS BY ROOTS OF Catunaregam uliginosa - SREEDEVI ADIKAY,; SRAVANTHI U, (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT: Objective: To evaluate the nephroprotective effect of ethanolic extract of roots of Catunaregam ulginosa in cisplatin induced nephrotoxicity in albino rats. Methodology: Ethanolic extract was prepared by hot extraction method and subjected to preliminary phytochemical studies. Based on acute toxicity studies nephroprotector was screened at two dose levels i.e., 200mg/kg bd wt and 400 mg/kg bd wt in both curative and prophylactic regimens. Cisplatin at a dose of 5mg/kg bd. wt was given intraperitoneally to induce nephrotoxicity. Nephroprotector activity was assessed by determining blood urea nitrogen (BUN), serum creatinine(SC), urinary total protein(UTP) and creatinine clearance. Antioxidant enzymes like super oxide dismutase (SOD), catalase (CAT), glutatathione reduced (GSH) activities and lipid peroxidation (LPO) levels were determined in renal tissue.Â  Histological studies had been carried per se. Results: Animals which received cisplatin exhibited significant increase in serum marker levels, increased urinary total protein excretion and reduced creatinine clearance. Further significant decrease in GSH, SOD, CAT and increase in LPO levels was observed. Ethanolic extract of roots of Catunaregam ulginosa reversed the effects induced by cisplatin in dose dependent manner in both curative and prophylactic regimens. Histological studies substantianed the above results. Conclusion: The findings of the present study support the alleviation of cisplatin induced nephrotoxicity by the ethanolic extract of roots of Catunaregam ulginosa and thus validate its ethnomedicinal use. Key words: Catunaregam ulginosa, Cisplatin, Nephrotoxicity, Lipid peroxidation